Cyprus: Island of Aphrodite II/ George Lanitis. IAPT Press: Nicosia, Cyprus. - Stylianou-Lambert, Theopisti (My University, 2020)
Cyprus: Island of Aphrodite II, published in 2020, is Stylianou-Lambert’s and Lambouris’ attempt to renegotiate their own visual past and a tribute to the creative process of photographic selection, exclusion and erasure. In what becomes an extended photographic act, the 1965 book is meticulously reproduced, only this time, ‘new’ photographs –photographs from Lanitis’ archive– are introduced and partially overlaid on top of the original pages; all the while, remaining aware of the fact that the mere act of overlaying material necessitates a much more violent act, that of erasure. As sociologist Andreas Panayiotou mentions in the introduction of Cyprus: Island of Aphrodite II: ‘The imposition of one picture on the other may shock the eye, and feel like a violation. The eye cannot see the older image in its totality. It can imagine it. But the artistic intervention is not only a negation. It is also a continuation. This is a book in which artists of the 21st century create a new paradox by adding archival photos, as if in a collage, to older, classical by now, “sacred” images.’